Effect of Iranian Honey bee (Apis mellifera) Venom on Blood Glucose and In- sulin in Diabetic Rats - SeyyedehMahbubeh Mousavi; Sohrab Imani; Saeid Haghighi; SeyyedehElaheh Mousavi; Akbar Karimi (Tehran University of Medical Sciences, 2015)
Background: Diabetes is an important disease. This disease is a metabolic disorder characterized by hyperglycemia resulting from perturbation in insulin secretion, insulin action or both. Honey bee venom contains a wide range of polypeptide agents. The principle components of bee venom are mellitin and phospholipase A2. These components increase insulin secretion from the β-cells of pancreas. This study was conducted to show the hypoglycemic effect of honey bee venom on alloxan induced diabetic male rats. Methods: Eighteen adult male rats weighting 200±20 g were placed into 3 randomly groups: control, alloxan mono- hydrate-induced diabetic rat and treated group that received honey bee venom daily before their nutrition for four months. Forty eight hours after the last injection, blood was collected from their heart, serum was dissented and blood glucose, insulin, triglyceride and total cholesterol were determined. Results: Glucose serum, triglyceride and total cholesterol level in treated group in comparison with diabetic group was significantly decreased (P< 0.01). On the other hand, using bee venom causes increase in insulin serum in com- parison with diabetic group (P< 0.05). Conclusion: Honeybee venom (apitoxin) can be used as therapeutic option to lower blood glucose and lipids in dia- betic rats.